No association of abnormal cranial venous drainage with multiple sclerosis: a magnetic resonance venography and flow-quantification study. Issue 4 (27th October 2010) - Wattjes, Mike P; van Oosten, Bob W; de Graaf, Wolter L; Seewann, Alexandra; Bot, Joseph C J; van den Berg, René; Uitdehaag, Bernard M J; Polman, Chris H; Barkhof, Frederik
Abstract : Background: Recent studies using colour-coded Doppler sonography showed that chronic impaired venous drainage from the central nervous system is almost exclusively found in multiple sclerosis (MS) patients. This study aimed to investigate the intracranial and extracranial venous anatomy and the intracerebral venous flow profile in patients with MS and healthy controls using magnetic resonance venography (MRV). Methods: Twenty patients with definite MS and 20 age- and gender-matched healthy controls were examined. MR imaging was performed on a whole-body 3T MR system including both 3D phase-contrast and dynamic 3D contrast-enhanced MRV as well as flow quantification of the internal cerebral veins and the straight sinus. Image analysis was performed by two experienced interventional neuroradiologists blinded to clinical data and structural brain imaging. The intracranial and extracranial neck veins were analysed for stenosis/occlusion and alternative venous drainage pattern. Results: A completely normal venous anatomy was observed in 10 MS patients and 12 controls. Anomalies of the venous system (venous stenosis/occlusions) were found in 10 MS patients and eight healthy controls. An anomalous venous system in combination with associated alternative venous drainage was observed in six MS patients and five healthy controls. Flow quantification showed no venous backflow in any MS patient or control. Conclusions: Findings suggestive of anomalies of the cranial venous outflow anatomy were frequently observed in both MS patients and healthy controls. Given the normal intracranial venous flow quantification results, it is likely that these findings reflect anatomical variants of venous drainage rather than clinically relevant venous outflow obstructions.